PENINGKATAN PEMAHAMAN GERAK SENI JURUS TUNGGAL PADA KELOMPOK KERJA GURU OLAHRAGA (KKGO) SE KECAMATAN RENGAT BARAT KABUPATEN INDRA GIRI HULU - Kamarudin Kamarudin; Yahyar Erawati; Zulrafli Zulrafli; Raihan Akbar Fajar; Muhammad Andrian (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Pencak silat is a martial arts system inherited by ancestors as the culture of the Indonesian nation so that it needs to be preserved, fostered, and developed. Martial arts is a martial arts movement that aims to protect yourself from things that are harmful and can threaten safety. Pencak silat also serves as a performing art, as a sport for physical freshness, matches and achievements and self-control, that is, the formation of personality, morals, character, faith and piety to God Almighty. The sport of martial arts is also included in the curriculum for learning physical education and health in schools. Pencak silat is a sports sport that is competed at the national and international levels. One of the categories competed in the pencak championship is the singles technique category. A single move is a martial arts match that features a martial artist demonstrating proficiency in a single standard move correctly, precisely and steadily and soulfully with his bare hands and armed. The purpose of this community service activity is to increase understanding of the movement of single moves in the working group of sports teachers in the west rengat district of Indra Giru Hulu Regency. The methods used in this service activity are conventional, namely material exposure, discussion and exercise